Protected rose cultivation for high income - Singh, M K; Raju, D V S; Sindhu, S S (Indian Horticulture, 2019)
The Rose is principal cut flower grown all over the country. It is generating more income and employment per unit area as compared to other crops. For cut flowers, old rose varieties like Super Star, Montezuma, Papa Meilland, Christian Dior, Eiffel Tower, Kiss of Fire, Golden Giant, Garde Henkel and First Prize are still in demand. In recent times, with production for export gaining ground in the country, the latest varieties like First Red, Grand Gala, Konfiti, Taj Mahal, Ravel, Tineke, Sacha, Prophyta, Pareo, Noblesse, Virsilia and Vivaldi etc. are also being grown commercially.